A Novel Method to Control the Crystallographic‐Preferred Orientation of Lead Iodide Toward Highly Efficient and Large‐Area Perovskite Solar Cells. Issue 10 (23rd August 2022) - Chiu, Pei-Ting; Tung, Yung-Liang; Wu, Shih-Hsiung; Hsu, Hung-Chieh; Huang, Kuo-Wei; Kuo, Ming-Tsun; Yang, Sheng-Hsiung
Abstract : Perovskite solar cells (PSCs) have been the promising stars in the solar cell industry for dramatically improving the power conversion efficiency (PCE) in the past decade and reaching a record over 25%. However, there are still many issues to be solved on an industrial scale. One of these challenges is the material stability of precursors, which may significantly affect the performance of PSCs. Herein, a facile method is provided to produce controllable lead iodide as the raw material for formamidinium‐based PSCs whose performance is highly correlated to the crystallographic‐preferred orientation of PbI2 . The PSCs based on the PbI2 synthesized at 120 °C exhibit the best PCE of 17.96% among these solar cells. Furthermore, the perovskite solar module with an active area of 3.68 cm 2 and a PCE of 16.08% is successfully demonstrated, showing the potential of scaling up in the future. Abstract : The proportion of the facet (001) of PbI2 crystals increases as the synthesis temperature increases and fabricates better formamidinium‐based perovskite films. The perovskite solar cells based on the PbI2 synthesized at 120 °C exhibit the best power conversion efficiency (PCE) of 17.96% and the module with an active area of 3.68 cm 2 shows a PCE of 16.08%.